Gas turbines : a handbook of air, land, and sea applications - Soares, Claire (Butterworth-Heinemann, 2008)
No other current publication offers the professional engineer or technician the wealth of useful guidance on nearly every aspect of gas turbine design, installation, operation, maintenance and repair as this bookdoes. Gas Turbines makes the job of any engineer involved in the design, selection, operation and maintenance of most nearly any type of gas turbine more efficient and more successful. The book offers the reader a big picture view of how to make the right decisions when planning what type of gas turbine to use for a particular application, taking into consideration not only operational requirements but long-term life-cycle costs in upkeep and repair and future usage. Concise overviews of all important theoretical bases in thermodynamics and fluid dynamics upon which gas turbine engines depend are presented. The author is an experienced industry consultant, with experience at such leading manufacturers of gas turbines as GE and Rolls Royce and relates how factors affect proper design, correct selection and specifications, and long-term successful operation for the application in question. The book offers professional engineers hard-to-find manufacturers data with extensive interpretation and explanation. Overview of major components, with a brief history of theory and development Important maintenance-related chapters Unique offering of manufacturer's specifications and performance criteria and future trends One-of-a-kind guidance on the economics and business management of turbine selection, as well as on installation and instrumentation/calibration.